2007
DOI: 10.1104/pp.107.102541
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Phosphoenolpyruvate Carboxylase Is Not Essential for High Photosynthetic Rates in the C4 Species Flaveria bidentis

Abstract: Phosphoenolpyruvate carboxylase (PEPC; EC4.1.1.31) plays a key role during C 4 photosynthesis. The enzyme is activated by metabolites such as glucose-6-phosphate and inhibited by malate. This metabolite sensitivity is modulated by the reversible phosphorylation of a conserved serine residue near the N terminus in response to light. The phosphorylation of PEPC is modulated by a protein kinase specific to PEPC (PEPC-PK). To explore the role PEPC-PK plays in the regulation of C 4 photosynthetic CO 2 fixation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Thus, phosphorylation seems to broaden the conditions under which PEPC can be active and seems to decrease the K m , while the V max of PEPC is only modestly affected Tovar-Méndez et al, 2000;Takahashi-Terada et al, 2005). Interestingly, the knockdown of PEPC phosphorylation in Flaveria bidentis (C 4 ) by RNA interference inhibition of PPCK did not affect the CO 2 assimilation rate, although the response to malate was observed as in previous studies (Furumoto et al, 2007). The latter indicates that phosphorylation is probably required to adjust PEPC activity in response to various signals or fluctuating conditions or to potentially mediate the interaction with another protein, such as 14-3-3 proteins (O'Leary et al, 2011;Grieco et al, 2012).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Thus, phosphorylation seems to broaden the conditions under which PEPC can be active and seems to decrease the K m , while the V max of PEPC is only modestly affected Tovar-Méndez et al, 2000;Takahashi-Terada et al, 2005). Interestingly, the knockdown of PEPC phosphorylation in Flaveria bidentis (C 4 ) by RNA interference inhibition of PPCK did not affect the CO 2 assimilation rate, although the response to malate was observed as in previous studies (Furumoto et al, 2007). The latter indicates that phosphorylation is probably required to adjust PEPC activity in response to various signals or fluctuating conditions or to potentially mediate the interaction with another protein, such as 14-3-3 proteins (O'Leary et al, 2011;Grieco et al, 2012).…”
supporting
confidence: 64%
“…The genus Flaveria is an exception, with only one characterized PPCK gene, encoding a 31.8-kD protein identified in F. trinervia and F. bidentis (Tsuchida et al, 2001;Furumoto et al, 2007). This raises the question of whether these species are a true exception in possessing only a single PPCK gene or if the nucleic acid sequences for further isoforms simply have been missed so far.…”
mentioning
confidence: 99%
“…All Flaveria species also possessed a PPCKB gene that displayed peak transcript abundance in the dark period and that was downregulated in the C 4 species relative to the C 3 species. Aldous et al (2014) suggested that the C 4 -recruited ppcA and PPCKA formed a coevolving substrate-kinase pair, and yet the findings of Furumoto et al (2007) argued that PPCKA in F. bidentis was dispensable for optimal CO 2 fixation via the C 4 pathway. Why would there be strong evolutionary selection acting on the C 4 ppcA/PPCKA substrate-kinase pair if the kinase and its phosphorylation of PPC were dispensable for optimal CO 2 fixation via the C 4 pathway?…”
Section: Discussion Physiological Consequences Of Loss Of Clock-contrmentioning
confidence: 99%
“…Previous work had shown that the PPCK gene responsible for light period phosphorylation and in vivo activation of photosynthetic PPC in the C 4 species Flaveria bidentis was not essential for high C 4 photosynthetic rates in this species (Furumoto et al, 2007). This work on a C 4 species surprised the wider community because decades of prior work had argued that PPC phosphorylation by PPCK was vital for alleviating malate/aspartate inhibition of PPC in planta and thus for optimizing photosynthetic CO 2 fixation in C 4 and CAM species (Vidal and Chollet, 1997;Nimmo, 2003).…”
Section: Discussion Physiological Consequences Of Loss Of Clock-contrmentioning
confidence: 99%
“…The nature of the controlling mechanisms for balance and coordination between the C 3 and C 4 cycles is still unclear, however, and concrete evidence for the coordinated regulation of primary carboxylation in the mesophyll and decarboxylation of C 4 acids in the bundle sheath has not been forthcoming. A key approach to revealing these mechanisms has been the use of antisense RNA in the C 4 dicot F. bidentis to reduce levels of key photosynthetic enzymes, including Rubisco (Furbank et al, 1996), NADP-malate dehydrogenase and pyruvate phosphate dikinase , Rubisco activase , carbonic anhydrase (Cousins et al, 2006), and PEPC protein kinase (Furumoto et al, 2007). This has proven to be a valuable method to help gain insight into enzyme function and regulation during C 4 photosynthesis and to potentially alter the balance between the C 3 and C 4 cycles.…”
mentioning
confidence: 99%